Impact of role stress, job burnout and job insecurity on job performance during pandemic COVID-19 among private hospital employees in Surakarta, Indonesia - Rachma, Ulfa Puspita; Sunaryo, Sinto (International Journal of Scientific Research and Management (IJSRM), 2022)
Pandemic COVID-19 has become a controversial issue resulting in radical shifts in people's lifestyles. Due to the situation, changes in management, followed by changes in employees' main duties and functions, may trigger employees' sense of uncertainty, which eventually affects their performance. This research focused on examining the impact of role stress, job burnout, and job insecurity on employee performance, with career calling as moderator. The research involved employees (health care and non-healthcare employees) at a private hospital in Surakarta, Indonesia. Data of 219 employees were taken by convenient sampling technique through questionnaires. The data were analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM) to determine the relationship among variables. The results indicated that: 1). Role stress significantly and positively affected job burnout and significantly and negatively affected job performance; 2). Job insecurity was found to significantly and positively affect job burnout and significantly and negatively affect job performance; 3). Job burnout was found to have a significant negative effect on job performance. Furthermore, the results suggested that career calling did not moderate the impact of role stress on job burnout. However, career calling was found to moderate the impact of role stress on job performance. The finding of this study is important in determining further steps related to job performance and its relationship with role stress, job burnout, career calling, and job insecurity.